Kemampuan Berpikir Kritis Matematis Siswa Dalam Model Pembelajaran Jucama pada Materi Trigonometri - Prihatiningtyas, Nindy Citroresmi; Rosmaiyadi, Rosmaiyadi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to determine the effect of Jucama learning model against students’ mathematical critical thinking abilities, the influence of Jucama learning models on students’ critical mathematical thinking abilities, completeness of student learning outcomes using Jucama models, the implementation of Jucama learning models, and students’ learning interest in Jucama learning models. This type of research is quantitative, the nonequivalent posstest-only control group design research. The study population was students of class X. The research sample taken was class X A as an experimental class and class X B as a control class. The research results are processed using independent statistical test sample t-test and effect size, one sample t-test, proportion test, and statistics descriptive. Based on the results of statistical tests on research data, it can be concluded that the Jucama learning model influences the ability to think critically mathematically, the Jucama learning model has a high effect on the ability to think critically mathematically, student learning outcomes experience completeness with the application of the Jucama learning model, the Jucama Jucama Learning model can be implemented well in its application and high student learning interest in the Jucama learning model.